2016
DOI: 10.1158/1078-0432.ccr-15-1617
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Regimen, Surgical Outcome, and T-cell Differentiation Influence Prognostic Benefit of Tumor-Infiltrating Lymphocytes in High-Grade Serous Ovarian Cancer

Abstract: Purpose: Tumor-infiltrating lymphocytes (TIL) are associated with a better prognosis in high-grade serous ovarian cancer (HGSC). However, it is largely unknown how this prognostic benefit of TIL relates to current standard treatment of surgical resection and (neo-)adjuvant chemotherapy. To address this outstanding issue, we compared TIL infiltration in a unique cohort of patients with advanced-stage HGSC primarily treated with either surgery or neoadjuvant chemotherapy.Experimental Design: Tissue microarray sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 29 publications
10
57
0
3
Order By: Relevance
“…By contrast, CD103+ TIL were mainly found in the tumor epithelium (Figure 1A). Total CD103+ TIL numbers did not differ significantly between patients that received PS or NACT therapy (not shown), as reported previously for epithelial CD8+ TIL in this cohort [12]. In line with the observed epithelial distribution, total CD103+ TIL counts per mm 2 in these patients correlated strongly to intraepithelial CD3+ and CD8+ TIL (r=0.86; p<0.0001 and r=0.87; p<0.0001, respectively), but weaker to stromal CD3+ and CD8+ TIL (r=0.14; p=0.0008 and r=0.59; p<0.0001, respectively) (Figure 1B and 1C).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…By contrast, CD103+ TIL were mainly found in the tumor epithelium (Figure 1A). Total CD103+ TIL numbers did not differ significantly between patients that received PS or NACT therapy (not shown), as reported previously for epithelial CD8+ TIL in this cohort [12]. In line with the observed epithelial distribution, total CD103+ TIL counts per mm 2 in these patients correlated strongly to intraepithelial CD3+ and CD8+ TIL (r=0.86; p<0.0001 and r=0.87; p<0.0001, respectively), but weaker to stromal CD3+ and CD8+ TIL (r=0.14; p=0.0008 and r=0.59; p<0.0001, respectively) (Figure 1B and 1C).…”
Section: Resultssupporting
confidence: 87%
“…First, we confirmed the recent reports on the prognostic benefit of CD103+ TIL in HGSC [7,11] in an independent cohort of advanced-stage HGSC patients treated with either primary surgery and adjuvant chemotherapy (PS; n=84), or neo-adjuvant chemotherapy followed by interval surgery (NACT; n=102) [12]. CD3+, CD8+ and CD103+ TIL were present in tumors from most patients and the distribution of CD3+ and CD8+ TIL in tumor epithelium and stroma was similar (Figure 1A).…”
Section: Resultssupporting
confidence: 87%
“…The presence of infiltrating immune cells in ovarian cancer was first reported nearly 40 years ago (15). Numerous studies elicited the favorable prognostic significance of increased numbers of various types of immune cells or overexpression of individual immune cell markers (9)(10)(11)(27)(28)(29). Our works revealed that the immune activation in HGSOC was an overall reaction of the host rather than a response of a single cell type or the expression alteration of a single gene.…”
Section: Discussionmentioning
confidence: 60%
“…Platelets may release growth factors such as transforming growth factor b (TGF-b), platelet-derived growth factor (PDGF), and vascular endothelial growth factor (VEGF), which may contribute to the growth, progression, and metastasis of the tumor by stimulating the proliferation of ovarian tumor cells 9 . Furthermore, a reduced lymphocyte count is an indicator of a reduced immune response, and it is correlated with higher mortality in patients with OC than in healthy controls or patients with benign diseases 10 . The PLR, which is inexpensively and easily determined in routine clinical practice, was proposed to be a highly efficient and independent prognostic biomarker for many tumors 7 .…”
Section: Introductionmentioning
confidence: 99%